Toleransi dan Keberagaman: Pilar Utama Persatuan Bangsa (Studi Hadis Tematik) - Ibia Zaynah; Muhammad Alif (AL-BAYAN INSTITUTE, 2023)
Tolerance and diversity are two fundamental values that underpin the creation of a peaceful and harmonious society, especially in a multicultural country like Indonesia. With over 1,300 ethnic groups and six official religions, Indonesia faces the challenge of maintaining harmony amidst its differences. This study aims to examine the role of the Hadiths of Prophet Muhammad SAW as a source of Islamic teachings in promoting tolerance and respecting diversity. The method used is a qualitative study with a descriptive-analytical approach, reviewing Hadiths related to tolerance and diversity from primary Hadith sources. The study finds that the principle of tolerance in Islam, as exemplified by Prophet Muhammad SAW, is manifested in mutual respect, both among Muslims and non-Muslims. The Hadiths not only provide ethical guidance for social interactions but also reinforce the view that diversity is part of divine decree that should be embraced with an open heart. The results of this study suggest that the application of these teachings can strengthen the unity of Indonesia’s diverse nation by emphasizing the importance of an inclusive attitude, mutual respect, and the promotion of peace in national life